2022
DOI: 10.1177/23779608221106444
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Social Support of Elderly Lung and Gastrointestinal Cancer Patients Undergoing Chemotherapy

Abstract: Introduction Increasing life expectancy has led to a higher incidence of cancer in the elderly, thus making them vulnerable and worsening their health-related quality of life (HRQoL) and their need for support. Objective The aim of this study was to examine the HRQoL and social support in elderly Greek lung and gastrointestinal cancer patients undergoing chemotherapy. Methods This was a descriptive, cross-sectional study of 104 elderly cancer patients, who were receiving chemotherapy in the outpatient departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Social support has long been noted as being beneficial [29], especially in health situations [30] and more specifically in the case of patients with cancer, survivors, and their loved ones [31][32][33]. In the digital era, social support can easily take place through technological mediums, whether through preplanned interventions or spontaneously through individual use [22,[34][35][36][37][38]. Our findings corroborate with this existing research in that the overwhelming majority of videos in our sample mentioned support, coping, and advocacy [39,40].…”
Section: Discussionsupporting
confidence: 88%
“…Social support has long been noted as being beneficial [29], especially in health situations [30] and more specifically in the case of patients with cancer, survivors, and their loved ones [31][32][33]. In the digital era, social support can easily take place through technological mediums, whether through preplanned interventions or spontaneously through individual use [22,[34][35][36][37][38]. Our findings corroborate with this existing research in that the overwhelming majority of videos in our sample mentioned support, coping, and advocacy [39,40].…”
Section: Discussionsupporting
confidence: 88%
“…There is a relationship between caregiver burden and anticipatory grief, with caregiver burden explaining about 36% of the variance in anticipatory grief, F = 6.343, p < 0.001, Adjusted R 2 = 0.36. Elderly cancer patients tend to suffer from fatigue, loneliness, nausea, vomiting, diarrhea, weight loss, anxiety, pain, depression, and multiple morbidities ( Kyriazidou et al, 2022 ). Therefore, caregivers need to provide long-term assistance with activities of daily living such as grooming, feeding, bathing, walking, and dressing ( Bonin-Guillaume et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is also a study that shows the connection between a lower level of social support and a significantly higher level of depression, suggesting that social support contributes to mental health and a higher quality of life ( Eom et al, 2013 ). Studies have shown that patients with strong social support develop more optimistic feelings, which enable them to increase their confidence and hope that they can successfully fight and cure cancer ( Kyriazidou et al, 2022 ). Studies examining the relationship between social support, depression, and quality of life in patients with various cancer diagnoses found that patients who did not have significant social support were more likely to suffer from depression, had lower functional abilities, and had a lower quality of life ( Korotkin et al, 2019 ), which is in line with the results of our reaserch in a statistically significant influence of the anxiety and depression as a predictor the bad social support.…”
Section: Discussionmentioning
confidence: 99%